2021
DOI: 10.14245/ns.2040452.226
|View full text |Cite
|
Sign up to set email alerts
|

National Trends and Correlates of Dysphagia After Anterior Cervical Discectomy and Fusion Surgery

Abstract: Anterior cervical discectomy and fusion (ACDF) is the most common performed surgery in the cervical spine. Dysphagia is one of the most frequent complications following ACDF. Several studies have identified certain demographic and perioperative risk factors associated with increased dysphagia rates, but few have reported recent trends. Our study aims to report current trends and factors associated with the development of inpatient postoperative dysphagia after ACDF. Methods: The National Inpatient Sample was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In the present study, we found a significantly higher incidence of complications in patients who underwent ACDF compared with those who underwent LAMP and LF, especially for dysphagia and pseudoarthrosis. Transient dysphagia was one of the most common postoperative complications following the ACDF procedure ( 23 ), a part of which was self-healing, whereas the others may suffer for a long time, severely impacting patients’ living quality. Because the site of operation and fixation with plate and graft were adjacent to the esophagus, patients who underwent the anterior cervical procedure were predisposed to suffer from dysphagia postoperatively, and this tendency was more evident as the operative segments increased ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found a significantly higher incidence of complications in patients who underwent ACDF compared with those who underwent LAMP and LF, especially for dysphagia and pseudoarthrosis. Transient dysphagia was one of the most common postoperative complications following the ACDF procedure ( 23 ), a part of which was self-healing, whereas the others may suffer for a long time, severely impacting patients’ living quality. Because the site of operation and fixation with plate and graft were adjacent to the esophagus, patients who underwent the anterior cervical procedure were predisposed to suffer from dysphagia postoperatively, and this tendency was more evident as the operative segments increased ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the secondary data lacked clinical and radiological information; hence, a detailed investigation and interpretation was not possible. Usually, reoperation and complication rates as well as incurred costs were used as a indicator for outcomes 32 , 33 , 37 , 46 , 59 . Morishita et al 2 analyzed nationwide inpatient data in Japan to compare anterior and posterior decompression and fusion.…”
Section: Discussionmentioning
confidence: 99%
“… 111 According to a recent study, 1,212,475 ACDFs were performed in the United States between 2004 and 2014, accounting for more than 80% of cervical spine procedures. 118 The United States still dominated the institution publications: 11 of the 15 most productive institutions were affiliated to the United States ( Table 3 ), explaining why the United States leads the world in total publications.…”
Section: Discussionmentioning
confidence: 99%